HYDROGEN AND OXYGEN ISOTOPE FRACTIONATION BETWEEN BRUCITE AND AQUEOUS NACL SOLUTIONS FROM 250 TO 450°C - 5. APPLICATIONS TO PHASE EQUILIBRIA, ISOTOPIC FRACTIONATION, AND HIGH PRESSURE THERMODYNAMIC PROPERTIES - Saccocia P.J.; Seewald J.S.; Shanks W.C. (My University, 1998)
Hydrogen and oxygen isotope fractionation factors between brucite and aqueous NaCl solutions (1000lnαbr-sw) have been calibrated by experiment from 250 to 450°C at 0.5 Kb. For D/H fractionation, 1000lnα br-sw values are as follows: -32 +/- 6%% (250°C, 3.2 wt% NaCl), -21 +/- 2%% (350°C, 10.0 wt% NaCl), and -22 +/- 2%% (450°C, 3.2 wt% NaCl), indicating that brucite is depleted in D relative to coexisting aqueous NaCl solutions. These results are in good agreement with previous D/H fractionation factors determined in the brucite-water system, indicating that any effects of dissolved salt on D/H fractionation are relatively small, particularly in solutions with near seawater salinity. The maximum salt effect (+4%%) was observed in 10.0 wt% NaCl solutions at 350°C, suggesting that the addition of dissolved NaCl increases the amount of deuterium fractionated into mineral structures. For 18O/16O fractionation, 1000lnαbr-sw values in 3.0 wt% NaCl solutions are -6.0 +/- 1.3%%, -5.6 +/- 0.7%% and -4.1 +/- 0.2%%, at 250, 350, and 450°C, respectively, and -5.8 +/- 0.6%% in 10.0 wt % NaCl at 350°C. These data indicate that brucite is depleted in 18O relative to coexisting aqueous NaCl solutions and that the degree of depletion decreases slightly with increasing temperature and is not strongly dependent on salinity. We calculated 18O/16O brucite-water fractionation factors from available calibrations of the salt-effect on 18O/16O fractionation between coexisting phases. The resulting values were fit to the following equation that is valid from 250 to 450°C 1000ln αbr-w = 9.54 x 106T-2 - 3.53 x 104T-1 + 26.58 where T is temperature in Kelvins. These new data have been used to improve the prediction of 18O/16O fractionation factors in the talc-water and serpentine-water systems by modifying existing empirical bond-water models. The results of this analysis indicate that the δ18O composition of talc-brucite and serpentine-brucite pairs could be used as a geothermometer and that these coexisting phases should display the following order of 18O enrichment: talc > serpentine > brucite.